Thema and world needs: exploring bibliodiversity through open access book subjects - Ronald Snijder (Insights: The UKSG Journal)
Bibliodiversity is mostly studied based on publication languages or the imbalance of the means of knowledge production and dissemination. This article explores the concept of bibliodiversity by analysing the consumption of open access books across different regions and examines the subjects of interest using the Thema classification system. The study deploys social network analysis to investigate affiliations between countries and book classifications, identifying clusters of shared interests. The results point to a correlation between regional proximity and subject interest.